SEMECARPUS ANCARDIUM LINN. : A POTENT HERBAL IMMUNOMODULATOR - BALAJI PANIGRAHI; MANISH VYAS (International Journal of Pharma and Bio Sciences, 2015)
Immunomodulation is a new area of interest to maintain health and sustainability. In order to boost immune system plants are more reliable source than synthetic and chemical agents because of less adverse effects. Therefore, extensive researches are being conducted on plants to get natural immunomodulators. Complementary and alternative medicine systems are renowned for using plant remedies for protection of health and eradicate diseases. Immunomodulation of these drugs are through not only by directly affecting the pathogen, but also by stimulating natural and adaptive defence mechanisms of the host. Ancient evidence and recent research suggest that single and compound formulations of Semecarpus anacardium Linn. can be a better alternate for conventional chemotherapy to treat various ailments. The aim of this review is to explore various researches carried out using Semecarpus anacardium Linn. for its immunomodulatory activity including its description, phytochemicals, pharmacological activities and therapeutic uses.